2010
DOI: 10.1152/ajplung.00422.2009
|View full text |Cite
|
Sign up to set email alerts
|

Expression of IL-4/IL-13 receptors in differentiating human airway epithelial cells

Abstract: and IL-13 elicit several important responses in airway epithelium including chemokine secretion and mucous secretion that may contribute to airway inflammation, cell migration, and differentiation. These cytokines have overlapping but not identical effector profiles likely due to shared subunits in their receptor complexes. These receptors are variably described in epithelial cells, and the relative expression, localization, and function of these receptors in differentiated and repairing epithelial cells are n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 71 publications
2
16
0
Order By: Relevance
“…IL-4 leads to the activation of multiple signaling pathways, including Stat6, CREB, NF-kB, and GATA3 (30)(31)(32), which induce eotaxin production. We used the software, TFSEARCH (version 1.3, Web site: http:// www.cbrc.jp/research/db/TFSEARCH.html), to predict the promoter region of PRMT1 and found that STATs, CREB, NF-kB, and GATA3 may combine with the promoter region of PRMT1.…”
Section: Discussionmentioning
confidence: 99%
“…IL-4 leads to the activation of multiple signaling pathways, including Stat6, CREB, NF-kB, and GATA3 (30)(31)(32), which induce eotaxin production. We used the software, TFSEARCH (version 1.3, Web site: http:// www.cbrc.jp/research/db/TFSEARCH.html), to predict the promoter region of PRMT1 and found that STATs, CREB, NF-kB, and GATA3 may combine with the promoter region of PRMT1.…”
Section: Discussionmentioning
confidence: 99%
“…Although IL-4 and IL-13 show similar effects on TJ in these airway epithelial cell models, depending on the investigated model, they act via different pathways. In Calu3 epithelia, IL-4 is reported to activate an EGFR-dependent MAPK/ERK1/2 pathway [100], whereas in human bronchial cell derived epithelia IL-4 as well as IL-13 act via the Janus kinase/signal transducer and activator of transcription (JAK/STAT) pathway [107], most likely via binding to the same receptor, namely heteromeric IL-13Rα/IL-4Rα receptor [139]. Indeed, both receptor subunits have an overlapping expression pattern in lung epithelia.…”
Section: Tight Junctions and Asthmamentioning
confidence: 99%
“…Indeed, both receptor subunits have an overlapping expression pattern in lung epithelia. IL-4Rα as well as IL-13Rα both were detected in human bronchial epithelial cells in vitro and in vivo [4, 46, 129, 133, 139]. IL-13Rα expression levels are increased in bronchial biopsy specimens from asthma patients which probably confers increased bronchial sensitivity to T H 2 cytokines [69].…”
Section: Tight Junctions and Asthmamentioning
confidence: 99%
“…Conventional PCR and Sequence Analysis IL-13, IL13Ra1, and IL13Ra2 expression was analyzed by RT-PCR with previously described primers (28)(29)(30). Primers specific for CD3g were forward 59-CCCAATG ACCAGCTCTACCA-39 and reverse 59-GGAACTGAATAGG AGGAGAACAC-39.…”
Section: Rna Extraction and Cdna Synthesismentioning
confidence: 99%